Disclosures and perceptions of practitioners on items of financial and social reporting index developed for Malaysian Islamic banks - Marsidi A.; Annuar H.A.; Abdul Rahman A.R. (Universiti Malaysia Sarawak, 2024)
Indexed by SCOPUS